Phytosociological analysis of pioneer woods on abandoned meadows in the Breginjski kot (western Slovenia) - Čušin, Boško; Dakskobler, Igor (Hacquetia, 2015)
Applying the standard Central-European phytosociological method we studied the floristic composition of pioneer stands of hazel (Corylus avellana) and European ash (Fraxinus excelsior) on abandoned meadows and pastures in the Breginjski kot region in the westernmost part of Slovenia (southwestern foothills of the Julian Alps). It was determined that most of the researched stands had developed on potential natural sites of the submontane beech forests from the alliance Aremonio-Fagion (Ht. 1938) Borhidi in Török, Podani & Borhidi 1989. They can be treated as a progressive successional stage Corylus avellana-Fraxinus excelsior or as a secondary forest community which we classified into the, for now only provisionally described, new association Ornithogalo pyrenaici-Fraxinetum excelsioris nom. prov.